Terrorism and Counterterrorism Studies Comparing Theory and Practice. 2nd Revised Edition. - Bakker, Edwin (Amsterdam University Press, 2022)
"Terrorism has arguably been one of the defining factors of our age. In many parts of the world, it has been one of the most important threats to peace, security and stability. But what does this exactly mean? What is the nature of this threat? What can be done about it or how can we at least limit the impact of terrorism? These are just a handful of questions that will be addressed in this book that consists of three parts. First it focuses on the essence of terrorism as an instrument to achieve certain goals and the difficulties in defining it. The second part provides an overview of the state of (counter)terrorism studies. The most interesting results of this academic field are examined and compared with empirical evidence with the aim to either stress their importance or to debunk them as myths. The final part looks into the implications and possibilities for policy making.